ANALYSIS OF COMMUNITY-BASED PEATLAND FIRE PREVENTION STRATEGIES - Harjanti, Diah Trismi; Medhina, Fidhi Melia; Fujianti, Lia Nurbanillah (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
Peatland  is a wetland ecosystem characterized by high organic matter accumulation and low decomposition rates. Rasau Jaya Tiga Village is one of the villages in the Rasau Jaya District with a soil type dominated by peat soil. Hence, the majority of its people are active in agriculture. As a form of effort to reduce the occurrence of land fires, it is necessary to conduct research on community-based peatland fire prevention strategies in the village of Rasau Jaya Tiga with a descriptive quantitative research type. The sample used was farmers in the village of Rasau Jaya Tiga with a data collection technique in the form of a community-based peatland fire prevention strategy questionnaire. The results showed that the most widely used strategy for preventing peatland fires was canal blocking or blocking canals, with 45 respondents. In comparison, the strategy for preventing land fires by pointing as many as 39 respondents, and the number of respondents with a strategy for preventing land fires using wood vinegar was 28, and as many as five respondents still use the strategy of burning the land in agricultural activities.